A Numerical Study of Hydraulic Fracture Propagation Geometry in a Layered Shale Reservoir. (15th March 2022) - Zhang, Lei; Jin, Yu; Dong, Zhuo; Yuan, Ruifu
Abstract : An unconventional shale reservoir commonly develops multiple layers and shows strong anisotropy in mechanical properties, which has a great effect on hydraulic fracture propagation geometry. The most common mechanical properties are elastic modulus, Poisson's ratio, tensile strength, and formation permeability. Therefore, the extended finite element method- (XFEM-) based cohesive zone model (CZM) is applied to analyze the effect of these mechanical properties on both the fracture propagation geometry and breakdown pressure in a layered shale reservoir after verifying the present numerical method by published analytical results. The parametric analysis indicates that the stiff or soft outer layers limit the fracture propagation width, while promoting the fracture propagation length. Higher Poisson's ratio and formation permeability in outer layers narrow the fracture propagation width in middle layer. Poisson's ratio contrast between different layers almost has no significant effect on the fracture propagation length and breakdown pressure. The hydraulic fracture propagation geometry presents the trend of "shorter and wider" with the increase of the tensile strength in outer layer. For asymmetric specimen with different mechanical parameters in each layer, hydraulic fracture shows an asymmetric propagation behavior, and hydraulic fracture preferentially propagates to the layer with higher elastic modulus, Poisson's ratio, formation permeability, and low resistance.